ANALISIS YURIDIS PENERAPAN MEDIASI PENAL OLEH KEPOLISIAN REPUBLIK INDONESIA DALAM PENYELESAIAN KASUS PIDANA DI INDONESIA - Doreswati, Dedy; Riyanto, Agus (SCIENTIA JOURNAL, 2019)
That is why in everyday life can catch various comments about a crime event that is different from one another. The research method used in this study is normative. The result of this research is that in this research the reasoning mediation that can be done is the complaint offense. Crimes that can be resolved by reasoning mediation are first a criminal offense or an offense such as the Complaints Against Humiliation or Defamation (Chapter XVI of the Criminal Code), a complaint regarding theft, extortion and threatening and embezzlement, a complaint about decency crime namely adultery. Second, Simple Delicacy (eencoudige delic) for example in Article 372 of the Criminal Code. The Third Criminal Act Has a Penal Penalty as the Threat of Criminal Offenders and Offenders Has Paid the Penalty. The fourth is Crime committed by Children. in the implementation of the Republic of Indonesia Police Investigator to provide training to investigators specifically dealing with child criminal cases and changing the retributive paradigm of the direction of the restoactive justice paradigm specifically in handling child criminal cases